Integrating the AHP and TOPSIS methods to select accounting staff - Anh Tuan Nguyen; Vo Van Tuyen (Decision Science Letters, 2025)
This study aims to select accountants for a business in Vietnam. The study engaged in focused discussions with experts to establish the criteria for an accountant. Next, structured interviews were conducted with experts to collect data comparing each pair of criteria and expert scoring data for each candidate according to each criterion. Then, the Analytical Hierarchy Process (AHP) was applied to determine the weight Wj of each criterion of an accountant, and finally the TOPSIS method was applied to find the similarity coefficient with the ideal solution Ci* for each candidate selection option. The result was that candidate A1 was selected because he had the highest Ci* coefficient of 0.81479; at the same time, through the weighted results Wj of the criteria, it showed that experts highly appreciated the candidate for the following outstanding characteristics: communication skills (W1 = 0.4108), professional skills (W4 = 0.2527), and personal skills (W2 = 0.1613).